The Influence of Head Teacher’s Leadership Styles on Service Delivery in Secondary Schools in Uganda: A Case Study of Ssembabule District. - Adoko, Vincent (Kabale University, 2023)
The study explored the influence of Head teachers’ leadership styles on service delivery in Secondary schools in Ssembabule district. The study was as a result of education performance and the quality of learning continuing to lag behind in Ssembabule district. The study used Cross- Sectional research design with both qualitative and quantitative approaches. The findings of the study indicates that under bureaucratic leadership, a high proportion of the respondents 24.6% agreed that Head teachers divide labor based on the functional specialization, 85 (35.0%) agreed that their schools have got a well-defined hierarchy of authority, 91 (37.9%) agreed with the statement that Head teachers practiced procedures for dealing with situation. 38.8% of the respondents under transactional leadership agreed that promotion and selection among teachers is based on technical competence that applied in the school. In addition, 40% agreed that Head teachers make clear expectations on what is to be done; this implies that with transactional leadership, school Head teachers have an important role in contributing to school planning and assisting the management of school resources The influence of Affiliative leadership was team building where by 45% of the respondents said that Head teachers does not spend time on team building, the other influence was responsibilities this was evidenced in table 5.0 where by 40% agreed with the statement that Head teachers shay away from their responsibilities and 37.3% also agreed that Head teachers create harmony and build emotional bond among teachers. The study found out that Head teachers’ leadership styles influences service delivery. The study found out that The Head teachers should consider the division of labor and specialization, as well as building well-defined hierarch of authority and taking regular feedback from the teachers and parents in order to improve the quality of service delivery in schools. The study recommended that Head teachers should work on their competences, consider team building, harmony, emotional bond among their teachers, understanding their responsibilities in order to improve on the quality of service delivery in schools.